2013
DOI: 10.1016/j.kjms.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of commercial citrate‐containing juices on urolithiasis in a Drosophila model

Abstract: Diet modification plays an important role in nephrolithiasis. Development of an easy, ready-to-use beverage such as a commercial juice drink to use as a preventive treatment for renal calculi formation would be widely welcomed. We previously developed a novel Drosophila model for the study of nephrolithiasis. It provides a new well-established drug discovery platform for this common disease. In our current study, we used the Drosophila model to investigate the preventive effects of various commercial juices as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…We used wild-type male D. melanogaster fed with 0.5% EG as lithogenic group and D. melanogaster fed without lithogenic agent as control group in this study for the evaluation of CaOx crystal formation [1719]. In brief, flies were bred in plastic vials containing a medium of yeast, corn syrup, and agar.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used wild-type male D. melanogaster fed with 0.5% EG as lithogenic group and D. melanogaster fed without lithogenic agent as control group in this study for the evaluation of CaOx crystal formation [1719]. In brief, flies were bred in plastic vials containing a medium of yeast, corn syrup, and agar.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have developed a fruit fly ( Drosophila melanogaster ) model for translational research of urolithiasis and applied this model to the evaluation of agents that may have potential antilithic effect [1719]. The Malpighian tubule of the fruit fly has a function similar to the human kidney [2023].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Drosophila calcium oxalate stone model has been used to screen traditional Chinese medicinal plants for the treatment of nephrolithiasis (Ho et al, 2013). Chen et al showed that commercial juices, such as apple, cranberry, orange, and pomegranate juices, failed to prevent calcium oxalate crystal formation in Drosophila nephrolithiasis model.…”
Section: Introductionmentioning
confidence: 99%